2010
DOI: 10.3171/2009.12.peds09173
|View full text |Cite
|
Sign up to set email alerts
|

Malignant transformation of an optic pathway glioma without prior radiation therapy

Abstract: Optic pathway gliomas (OPGs) arise from the optic nerves, optic chiasm, and/or hypothalamus and most commonly occur in childhood. Although these tumors can be quite challenging to manage, they are typically low-grade astrocytomas histologically, most commonly pilocytic astrocytomas. The few previously reported cases of malignant degeneration of an OPG occurred after external beam radiation therapy. The authors report the first case in the English literature of an OPG that transformed from a low-grade a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 18 publications
0
15
0
1
Order By: Relevance
“…Longterm survivors of radiation in childhood remain at risk for the subsequent development of additional tumors such as meningiomas and other glial neoplasms. 19,28,31 Weprin et al 30 reported on 3 patients with recurrent pediatric ependymomas treated using SRS, with 2 patients having poor outcomes. One patient survived, 1 died of disease progression, and 1 died of radiation necrosis.…”
Section: Stereotactic Radiosurgery As Adjuvant Management For Recurrementioning
confidence: 98%
“…Longterm survivors of radiation in childhood remain at risk for the subsequent development of additional tumors such as meningiomas and other glial neoplasms. 19,28,31 Weprin et al 30 reported on 3 patients with recurrent pediatric ependymomas treated using SRS, with 2 patients having poor outcomes. One patient survived, 1 died of disease progression, and 1 died of radiation necrosis.…”
Section: Stereotactic Radiosurgery As Adjuvant Management For Recurrementioning
confidence: 98%
“…Moharir et al [21] used positron emission tomography and computed tomography to follow 18 patients with optic pathway gliomas, 3 of whom were reported as having high-grade tumors. Zoeller et al [22] recently reported the first case of malignant transformation of an optic pathway glioma in the absence of radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Optik sinir gliomunda tedavi yöntemi olarak izlem, eksternal radyoterapi ve kemoterapi uygulanabilir. 7,11 Gliomlarda tedavi tümörün kiazmayı tehdit edip etmemesine, görme keskinliğine ve tümörün neden olduğu komplikasyonlara bağlı olarak değişir. Bazı hastalarda tümör kendiliğinden gerileyebilir.…”
Section: Sonuçlarunclassified